Dry matter accumulation and carbohydrate composition of a new cultivar of maize, "Sugary-Opaque-2-Waxy". - Machado, Magali C. M. S. T; Reyes, Felix G. R.; Silva, Willian J. da (Pesquisa Agropecuaria Brasileira, 2014)
Dry matter accumulation and carbohydrate composition of a new cultivar of maize (Zea mays L.), te triple mutant Sugary-Opaque-2-Waxy, was comparatively studied in relation to the cultivars Sugary, Opaque-2, Waxy,Sugary-Opaque-2 and Maya Normal in general, all cultivars showed similar content of soluble reducing sugars. The cultivars with te sugary gene showed higher content of total soluble sugars and phytoglycogen than those with the starchy endosperm. The opposite was found to te starch content Maya Normal and te triple mutant showed, respectively, te higher and lower values for dry matter accumulation at the different stages of endosperm development (15, 20, 25, 30 and 35 days after poilination - DAP). The lower rate of dry matter accumulation suggests that te triple mutant would be more appropriate to be consumed as sweet corn.